Investigating Processes of Nanocrystal Formation and Transformation via Liquid Cell TEM. (14th March 2014) - Nielsen, Michael H.; Li, Dongsheng; Zhang, Hengzhong; Aloni, Shaul; Han, T. Yong-Jin; Frandsen, Cathrine; Seto, Jong; Banfield, Jillian F.; Cölfen, Helmut; De Yoreo, James J.
Abstract Recent ex situ observations of crystallization in both natural and synthetic systems indicate that the classical models of nucleation and growth are inaccurate. However, in situ observations that can provide direct evidence for alternative models have been lacking due to the limited temporal and spatial resolution of experimental techniques that can observe dynamic processes in a bulk solution. Here we report results from liquid cell transmission electron microscopy studies of nucleation and growth of Au, CaCO3, and iron oxide nanoparticles. We show how these in situ data can be used to obtain direct evidence for the mechanisms underlying nanoparticle crystallization as well as dynamic information that provide constraints on important energetic parameters not available through ex situ methods.